Modelling and mapping of soil erosion in the north-eastern frontier Himalayan ranges of India using remote sensing and GIS - VANLALCHHUANGA,; JENA, ROOMESH KUMAR; MOHARANA, P.C.; KUMAR, NIRMAL; SHARMA, RAM PRASAD; DAS, BACHASPATI; ROY, PARTHA DEB; RAY, SANJAY KUMAR (Journal of Soil and Water Conservation, 2023)
Soil erosion is a land degradable problem cause by natural resources. In context of North Eastern Himalayan ranges, it is a common soil degradation process due to fragile nature of soil and ecosystem. The aim of this study is to assess the soil erosion of Mahadevpur block, Namsai district of Arunachal Pradesh by RUSLE method using remote sensing and GIS environment. In this study, Sentinel 2 data of the study area was used to prepare land use/land cover (LU/LC) map by visual interpretation technique and ALOS digital elevation model (DEM) was used to develop slope, contour, flow direction and flow accumulation maps. Thematic raster layers of RUSLE factors (R, K, LS, C and P) were computed and used to estimate average annual soil loss by ArcGIS 10.3 software. The results showed that maximum area was (37.10%) under very slight soil loss class (< 5.0 t ha-1 yr-1). However, the extremely severe soil loss(> 80.0 t ha-1 yr-1) was observed in 7.0 % of the study area which was confined to terrain features such as lateral bar, meander scar, point bar, braided bar and channel bar. It was proved that, use of geospatial technologies in combination with RUSLE is a comprehensive approach, which helped in spatial assessment of soil erosion for better resource planning and taking up suitable conservation measures.